A fluorene-core-based electron acceptor for fullerene-free BHJ organic solar cells—towards power conversion efficiencies over 10%. Issue 32 (4th April 2018) - Suman,; Bagui, Anirban; Garg, Ashish; Tyagi, Barkha; Gupta, Vinay; Singh, Surya Prakash
Abstract : A small molecule non-fullerene electron acceptor (SMNFEA), bearing a furan π-spacer and dicyano- n -hexyl rhodanine as flanking groups, was designed and synthesized for organic solar cell applications. Abstract : A small molecule non-fullerene electron acceptor (SMNFEA), bearing a furan π-spacer and dicyano- n -hexyl rhodanine as flanking groups, was designed and synthesized for organic solar cell applications. Organic photovoltaic devices based on FRdCN2 and PTB7-Th polymer donors exhibited a highly improved efficient power conversion efficiency of 10.7%, which is the highest so far for OSCs fabricated from fluorene-core-based SMNFEAs.